Debt Refinancing and Equity Returns - FRIEWALD, NILS; NAGLER, FLORIAN; WAGNER, CHRISTIAN (Journal of Finance, 2022)
ABSTRACT This paper presents empirical evidence that the maturity structure of financial leverage affects the cross‐section of equity returns. We find that short‐term leverage is associated with a positive premium, whereas long‐term leverage is not. The premium for short‐term compared to long‐term leverage reflects higher exposure of equity to systematic risk. To rationalize our findings, we show that the same patterns emerge in a model of debt rollover risk with endogenous leverage and debt maturity choice. Our results suggest that analyses of leverage effects in asset prices and corporate financial applications should account for the maturity structure of debt.